Faktor-Faktor Yang Berhubungan Dengan Kegemukan Pada Balita di Kelurahan Warnasari Kecamatan Citangkil Kota Cilegon - Sari Suriani (Faletehan Health Journal, 2019)
More nutritional status is a condition where body weight exceeds the normal weight standard. More nutrition can occur at all ages, from babies, toddlers, children, adults and the elderly. Nutritionists association of Cipto Mangun Kusumo Hospital (RSCM), said that more nutrition that can cause obesity at the age of toddlers, has the potential to cause an increased risk of degenerative diseases, respiratory problems, heart problems and can be at risk of developing diabetes. This study aims to determine the relationship of fatigue in toddlers in Warnasari Village, Citangkil Subdistrict, Cilegon City. The sample in this study were toddlers aged 24-59 months, obtained as many as 94 toddlers. The results of this study showed that there were 18 children under five or 19.1% of children under five in the obese category, there were 60.6% of children under five who were male, birth weight at risk there were 16.0% of children under five, and 13.8% of children under five who works, 76.6% of education for under-five mothers who have higher education, and 75.5% of under-five families who have a family of <4 or a small family. There is a relationship between sex (pv: 0.003), birth weight (pv: 0.00), maternal work (pv: 0.00) with obesity in children under five. There is no relationship between education and the number of family members with obesity in children under five. It was suggested that the Health Service should make an effort to prevent obesity in children under five through monitoring and evaluating obesity.